Religija ir kultūra : mokslo žurnalas : scholarly journal - Vilniaus Universitetas - Filologijos Fakultetas (2006)
"Religija ir kultūra (Eng. Religion and Culture) is an interdisciplinary journal publishing original scholarly articles and research papers devoted to research the phenomenon of religion and the relationship between religion and culture, by integrating religious studies, philosophy of religion, etc. disciplines. The journal also publishes translations of the original texts, book reviews, and the chronicle of academic life. The submissions are subject to double-blind peer-review by two scholars"